Prolapsed Lumbar Intervertebral Disc (PLID) Surgery and Our Experiences - Islam, Md Shoriful; Quader, Md Abdul; Haq, K M Reza Ul; Rana, Md Masud; Marium, Hafsa (Delta Medical College Journal, 2024)
Background: Herniated lumbar disc is the most common specific cause of low back pain. Surgery results in better outcome for cases with exclusive severe radicular pain and health-related quality of life improves after lumbar disc herniation (LDH) surgery. Objective: To determine the outcome of lumbar disc herniation surgery and to assess the effect of factors that could predict the outcome of surgery. Materials and method: This observational study was done in Delta Medical College & Hospital, Mirpur, Dhaka, during March 2016 to January 2019. We evaluated 54 patients who had undergone operations for lumbar disc herniation using three different surgical techniques (laminectomy, fenestration and discectomy, and spinous process osteotomy) for low back pain and radicular pain. Results: Forty six (85.19%) patients were male and 8(14.81%) were female. Age range was 18-60 years. Forty nine (90.74%) were new patient and 5(9.26%) had recurrent disc prolapse. Diagnosis was confirmed by MRI. Fifty (92.59%) patients had no pain after surgery and only 2(3.70%) patients needed reoperation and 2(3.70%) had occasional pain. Conclusion: Surgery for lumbar disc herniation is effective in reducing radicular pain. All three surgical approaches resulted in significant decrease in preoperative radicular pain and low back pain, but 100% good outcome was not achieved. Delta Med Col J. Jan 2021;9(1): 28-32